COMPARATIVE EFFECTIVENESS OF DIFFERENT METHODS OF CANDIDAL DYSBACTERIOSIS THERAPY - S.V. Nikolaeva; A.V. Gorelov ("Paediatrician" Publishers LLC, 2009)
The study of effectiveness of different methods of microbiological disorders correction in children after 3 years old with candidal dysbacteriosis are presented in this article. The study compared probiotical sour milk-made stuff («Actimel») and sour milk-made stuff, not fortified with probiotical cultures («Rastishka» and traditional kefir). It was shown that an inclusion of probiotical sour milkmade stuff in diet of children with candidal dysbacteriosis results in normalization of lacto- and bifidobacteria level and decreasing of Candida level. Key words: children, candidal dysbacteriosis, probiotics. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(6):31-35)